Severe visual impairment: practical guidance for paediatricians. Issue 8 (August 2018) - Oluonye, Ngozi; Sargent, Jenefer
Abstract: Visual impairment is generally categorised, along with hearing impairment, as a sensory disorder. Vision is arguably the dominant human input sense, and supports the development of cognitive, language and social skills as well as early emotional bonding and later literacy and independent mobility. Vision however also drives the integration of input from other senses and limitations in vision presents the infant with significant challenges in making sense of what is heard or touched. Severe visual impairment consequently has a significant impact on multiple aspects of early development and challenges continue throughout childhood. It is more appropriate therefore to think of severe visual impairment as a potential neurodevelopmental disorder, which requires ongoing input from a range of professionals. Paediatricians play a key role not only in the early detection of severe visual impairment arising from primary visual disorders but also in the assessment and ongoing management of the developmental consequences. Severe visual impairment may be underdiagnosed in children with complex neurological impairment even in those already known to the Eye clinic. Paediatricians can play a crucial role in identifying possible visual difficulty, during early follow up of those at risk of neurological impairment, or via ongoing review of those with established complex disability.